Hybridizing China in Zhang Yimou’s hero (2002) - Kim, Eun-hae (2016)
Access online through this link: https://www.plarideljournal.org/article/hybridizing-china-zhang-yimous-hero-2002
Keywords: Motion picture industry -- China; Filmmaking; Film reviewing